The Quantitative Analysis of Traffic Movement Standards and Communication on the Rural Road Network in Salah al -Din Governorate - Saleh, Qahtan Hamad; Abdullah, Sabah Othman (Journal of Tikrit University for Humanities, 2025)
Traffic is an indicator for revealing the dimensions of spatial relationships between rural settlements and urban centers, and it shows the extent of vehicle traffic pressure on roads, as well as assessing the efficiency and adequacy of these roads. Therefore, traffic density on road networks varies due to three factors: population size, the area served by the road, and the length of the road. It can also be defined as the total number of vehicles passing a specific point or along a specific road in road networks over a certain period, which can be expressed on a yearly, daily, or hourly basis and its subdivisions. To study the size of daily traffic for vehicles and passengers, a field survey was conducted on important rural roads that connect rural areas to urban centers, where specific monitoring locations were identified. The study included 28 rural roads that represent the most trafficked rural routes for vehicles and passengers in Salah al-Din Governorate, and its results cover most parts of the governorate. Table (1) shows the names of the studied roads and their coordinates, while the monitoring hours were represented during the morning and evening peaks at three times to determine the volume of traffic on rural roads in order to extract the daily average of the number of vehicles and passengers on those roads. The movement and communication metrics of the rural road network in Salah al-Din Governorate have been studied, as they are of great importance in the field of transportation geography.